Unprecedented Electromagnetic Shielding Effectiveness of Lightweight Nonwoven Ag/PA66 Fabrics - SANCAK, ERHAN; ÖZEN, MUSTAFA SABRİ (KOREAN FIBER SOC, 2018)
Novel, high-performance silver coated polyamide, Ag/PA66, nonwoven fabrics with a density of only 0.04 g/cm(3) have been developed using staple fibres of 19 (3.3 dtex) and 27 (6.7 dtex) mu m diameter. The obtained nonwoven fabrics with an Ag loading of 12-18 wt% exhibited excellent weight-normalised specific electromagnetic shielding effectiveness of over 1200 dB/(g/cm(3)) in the 0.015-3 GHz range, which is among the highest reported till date. Moreover, the applied microwave was verified to be absorbed rather than being reflected back making the fabrics highly suitable for shielding applications. It was also observed that nonwoven fabrics made from finer 3.3 dtex Ag/PA66 fibres have higher reflection and lower absorption values than their thicker (6.7 dtex) counterparts. Additionally, we have also explored the use of these nonwoven Ag/PA66 fabrics for personal thermal management via Joule heating with samples showing rapid heating response (up to 0.2 degrees C/sec) and long-term stability measured over 10,000 seconds. The needle-punched Ag/PA66 nonwoven fabrics, in spite of their low density of the order of 0.04 g/cm(2), exhibited high EMSE values of nearly 69-80 dB, leading to excellent weight-normalised specific electromagnetic shielding effectiveness of over 1200 dB/(g/cm(3)) in the 0.015-3 GHz range. The production of Ag/PA66 needle punched nonwoven fabrics thus offers a facile route to develop multifunctional fabrics for EMI shielding as well as personal thermal management applications.
Keywords: Ag/PA66 fibres; Nonwoven; Needle punching; Electromagnetic shielding; Joule heating; Thermal management; SILVER NANOPARTICLES; STAINLESS-STEEL; COMPOSITE FOAMS; TEXTILE; FIBERS; ANTIBACTERIAL; YARNS; DEPOSITION; BEHAVIOR